2023
DOI: 10.1101/2023.10.20.563319
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A public resource of single cell transcriptomes and multiscale networks from persons with and without Alzheimer’s disease

Qi Wang,
Jerry Antone,
Eric Alsop
et al.

Abstract: The emergence of technologies that can support high-throughput profiling of single cell transcriptomes offers to revolutionize the study of brain tissue from persons with and without Alzheimer's disease (AD). Integration of these data with additional complementary multiomics data such as genetics, proteomics and clinical data provides powerful opportunities to link observed cell subpopulations and molecular network features within a broader disease-relevant context. We report here single nucleus RNA sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 96 publications
(145 reference statements)
0
8
0
Order By: Relevance
“…To examine the effect of APOE2 in the aging human brain, we investigated the single-nucleus RNA sequencing dataset of 52 individuals, which included 25 APOE2/3-carriers and 27 APOE3/3-carriers, randomly chosen from the ROSMAP. Among the 52 individuals, half exhibited high levels of β-amyloid and other pathological hallmarks of Alzheimer’s disease ('AD-pathology', 'AD'), while the remaining half showed either no or low β-amyloid burden ('non-AD-pathology', 'nonAD'), which aligned with the NIA-AA criteria [ 18 , 38 , 39 ]. Both APOE3/3 and APOE2/3 groups maintained a balance in terms of AD pathology, gender (APOE2/3: 11 males and 14 females, APOE3/3: 12 males and 15 females), age (median: 86.78 APOE2/3, 85.76 APOE3/3), years of education (median: 16.20 APOE2/3, 16.04 APOE3/3), and post mortem interval (PMI) (median: 7.245 APOE2/3, 8.026 APOE3/3) (Fig.…”
Section: Resultsmentioning
confidence: 64%
“…To examine the effect of APOE2 in the aging human brain, we investigated the single-nucleus RNA sequencing dataset of 52 individuals, which included 25 APOE2/3-carriers and 27 APOE3/3-carriers, randomly chosen from the ROSMAP. Among the 52 individuals, half exhibited high levels of β-amyloid and other pathological hallmarks of Alzheimer’s disease ('AD-pathology', 'AD'), while the remaining half showed either no or low β-amyloid burden ('non-AD-pathology', 'nonAD'), which aligned with the NIA-AA criteria [ 18 , 38 , 39 ]. Both APOE3/3 and APOE2/3 groups maintained a balance in terms of AD pathology, gender (APOE2/3: 11 males and 14 females, APOE3/3: 12 males and 15 females), age (median: 86.78 APOE2/3, 85.76 APOE3/3), years of education (median: 16.20 APOE2/3, 16.04 APOE3/3), and post mortem interval (PMI) (median: 7.245 APOE2/3, 8.026 APOE3/3) (Fig.…”
Section: Resultsmentioning
confidence: 64%
“…The emergence of large-scale single nuclei RNAseq (snRNAseq) data generated from post-mortem brain tissue from subjects affected by AD has offered new approaches for characterizing AD-associated molecular networks in a cell-specific manner. We recently generated snRNAseq superior frontal gyrus (SFG) profiles from 101 exceptionally well characterized subjects 50 , and interrogated this data to examine AD-associated Src mRNA expression in a cell-type specific manner. Consistent with our histochemical and protein quantification analyses, we observed that Src is significantly upregulated in excitatory neurons (Ex).…”
Section: Resultsmentioning
confidence: 99%
“…Detailed clinical data, postmortem neuropathological data, and demographics of the cohort are described in. 29 We constructed gene co-expression and detected multiscale gene modules using MEGENA 30 on the differentially abundant excitatory neurons, which were identified as those neurons in control subjects most susceptible to neuronal loss in AD. Differential expression of genes between AD vs control was identified by the FinderMarkers function of the Seurat (v4.0) workflow 31 , using the MAST algorithm 32 .…”
Section: Double Label Immunohistochemistrymentioning
confidence: 99%
“…It plays a role in the regulation of neurotransmitter release at synapses [66] although there is limited study for its characterization. Its expression has been found to be positively correlated with cognitive function and consistently downregulated in multiple neuron subtypes from AD brains especially in females, in numerous transcriptomic profiles by snRNAseq [53,[67][68][69]. Further characterization of the transcript and protein and their roles in neurological function and disorder is thus warranted.…”
Section: Discussionmentioning
confidence: 99%